Frontopolar Cortex Specializes for Manipulation of Structured Information - Kroger, James; Kim, Chobok (Frontiers in Systems Neuroscience, 2022)
We present a review of the literature on the function of frontopolar cortex from the last 20 years, then support conclusions from it by presenting an original empirical study. Considerable research has focused in the last decade on a hierarchical organization of cognitive function in the frontal lobes, with simple motor response mapping occurring in the posterior areas of the frontal lobes, and increasingly abstract responses involving increasingly anterior regions. The frontopolar cortex (FPC), Brodmann's Area 10, is most often found to be recruited by the most abstract varieties of processing. We discuss the nature of abstractness or complexity by which these hierarchical schemes are defined. We then report our study whose results suggest that the anterior frontal lobe is not specialized for processing and responding about the most abstract information, but is recruited when one must manipulate relationally complex information. Simply encoding or maintaining abstract or complex information is accomplished by the dorsolateral prefrontal cortex (DLPFC). In the course of everyday reasoning, we must manipulate, rearrange, juxtapose, or restructure complex information. The ability to do this with complex information allows humans to navigate complex problems or situations better than higher primates. It permits the production of novel, complex solutions to complex challenges. Our results suggest that it is the frontal pole which is recruited when such manipulation and restructuring of represented information is needed.